Constructing validity for capabilities-related indicators - Cecilia Tinonin (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
Amartya Sen's approach to Welfare Economics argues evaluation of individual advantage should occur in the informational space of the freedom of choice individuals have in achieving valuable human functionings, that is in the space of capabilities. Furthermore, the identification of what is valuable involves taking into account ethical reasoning in the explanation of actual human behaviour, that is agency freedom, as well as the variety of human values. Despite of the recognition of such contribution to Economic Theory, unavailability of appropriate data and indicators challenges empirical investigations. This paper aims at overcoming such shortcoming through an assessment of the validity of an indicator measuring agency freedom as empowered autonomous choice. The empirical investigation is conducted on a random sample of 136 women in a rural patriarchal village in Uttar Pradesh, India, through a multi-topic survey instrument. Results indicate agency freedom differs across domains. In particular, individuals ranking high in the domain of resources simultaneously rank lower in the domain of empowerment. Furthermore, empirical evidence suggests a phenomenon of social exclusion of those more autonomous. Therefore, policy prescriptions at the community level identify enhancing collective capabilities as a viable strategy to accommodate the simultaneous coexistence of empowerment and social inclusion as well as the enhancement of principles of social justice rooted in a freedom-related metric.
Keywords: D69; I32; 330